Energy Efficiency Analysis in Air Conditioning Systems Using the Thermodynamic Cycle Method - Wulan Febriyani; Linda Purwanti; Ria Fitri Mawardiningrum (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Energy efficiency in air conditioning systems is a critical factor in reducing energy consumption and environmental impact. This study aims to analyze the energy performance of an air conditioning system using the thermodynamic cycle method. The analysis focuses on the refrigeration cycle, particularly the vapor compression cycle commonly used in residential and commercial systems. Key parameters such as coefficient of performance (COP), refrigerant flow rate, and enthalpy at each cycle point were examined to determine overall efficiency. Data were collected through simulations and experimental measurements under standard operating conditions. The results show that optimizing system components, especially the compressor and expansion valve, can significantly improve energy efficiency. The COP increased by 12% when a high-efficiency compressor was utilized. In addition, the selection of eco-friendly refrigerants contributed to better thermal performance and reduced environmental risks. This research highlights the importance of thermodynamic analysis in designing and improving air conditioning systems for sustainable energy usage. Future studies are recommended to incorporate real-time monitoring and adaptive control systems to further enhance system performance and energy savings.